Effect of Health-Education Intervention on Knowledge Level and Motivation of Hypertension Prevention among Pre-Hypertensive Market Traders in Lagos State - Oyerinde, Oyewole Olusesan; Okesiji, Idowu Omotunde; Amosu, Ademola Mufutau (NIU Journal of Social Sciences, 2023)
Hypertension is a long-term medical disorder in which blood pressure in the arteries remains abnormally high (Naish & Court, 2014). Majority of the time, high blood pressure is asymptomatic (Ayogu, Ezeh & Okafor, 2021). Nevertheless, persistent, uncontrolled high blood pressure is a major risk factor for cardiovascular diseases such as stroke, coronary artery disease, heart failure, atrial fibrillation and peripheral arterial disease. It also predisposes to vision loss, chronic kidney disease and dementia (Lackland & Weber 2015; Mendis, Puska & Norrving 2011; Hernandorena, Duron, Vidal & Hanon 2017; Lau, Nattel, Kalman & Sanders 2017). It accounts for significant cases of premature mortality worldwide (GBD, 2015; Mills, Obst, Shen, Molina, Zhang, He, Cooper, & He 2016).